Pengaruh BTS Sebagai Brand Ambassador Tokopedia Terhadap Keputusan Pembelian - Savrila Sekar Alifia Wibowo; Abdul Yusuf (Peneliti.net, 2023)
Nowadays the trend of online shopping (Online Shopping) is increasingly widespread in almost all circles of society. So that more and more parties are trying to provide containers that allow transactions between sellers (E-commerce) and buyers through networks or known as Marketplaces to occur. Tokopedia is one of the Marketplaces that competes with business actors in the same field. As a marketing strategy, Tokopedia recruited a Korean boy group named BTS as a digital Brand ambassador aimed at winning the competition. This study aims to prove the influence of BTS as Tokopedia's brand ambassador on purchasing decisions. As sampling, this study used Tokopedia users and/or BTS fans who are over 16 years old. The analytical technique used is Multiple Linear Regression, which will make it easier to see the role of BTS as Tokopedia's brand ambassador for purchasing decisions to be tested. The test results show that the use of BTS as Tokopedia's brand ambassador has an effect on purchasing decisions at Tokopedia.